RET fusions in a small subset of advanced colorectal cancers at risk of being neglected. (10th March 2018) - Pietrantonio, F; Di Nicolantonio, F; Schrock, A B; Lee, J; Morano, F; Fucà, G; Nikolinakos, P; Drilon, A; Hechtman, J F; Christiansen, J; Gowen, K; Frampton, G M; et al.
Abstract: Background: Recognition of rare molecular subgroups is a challenge for precision oncology and may lead to tissue-agnostic approval of targeted agents. Here we aimed to comprehensively characterize the clinical, pathological and molecular landscape of RET rearranged metastatic colorectal cancer (mCRC). Patients and methods: In this case series, we compared clinical, pathological and molecular characteristics of 24 RET rearranged mCRC patients with those of a control group of 291 patients with RET negative tumors. RET rearranged and RET negative mCRCs were retrieved by systematic literature review and by taking advantage of three screening sources: (i) Ignyta's phase 1/1b study on RXDX-105 ( NCT01877811 ), (ii) cohorts screened at two Italian and one South Korean Institutions and (iii) Foundation Medicine Inc. database. Next-generation sequencing data were analyzed for RET rearranged cases. Results: RET fusions were more frequent in older patients (median age of 66 versus 60 years, P  = 0.052), with ECOG PS 1–2 (90% versus 50%, P  = 0.02), right-sided (55% versus 32%, P  =   0.013), previously unresected primary tumors (58% versus 21%, P  <   0.001), RAS and BRAF wild-type (100% versus 40%, P  < 0.001) and MSI-high (48% versus 7%, P  <   0.001). Notably, 11 (26%) out of 43 patients with right-sided, RAS and BRAF wild-type tumors harbored a RET rearrangement. At a median follow-up of 45.8 months, patients with RET fusion-positive tumors showed a significantly worse OS when compared with RET -negative ones (median OS 14.0 versus 38.0 months, HR: 4.59; 95% CI, 3.64–32.66; P  <   0.001). In the multivariable model, RET rearrangements were still associated with shorter OS (HR: 2.97; 95% CI, 1.25–7.07; P  =   0.014), while primary tumor location, RAS and BRAF mutations and MSI status were not. Conclusions: Though very rare, RET rearrangements define a new subtype of mCRC that shows poor prognosis with conventional treatments and is therefore worth of a specific management.